Personalised Medicine Approaches to Screening and Prevention. Issue 1 (2nd January 2017) - Gaitskell, Kezia
Abstract : One of the promised benefits of 'personalised' medicine is that it will have a positive impact on disease screening and prevention, by enabling more person-specific estimates of risk, and hence more personalised strategies for screening and risk reduction. This article summarises some of the areas in which these approaches are already being implemented, but also outlines some of the potential difficulties and limitations — and challenges the assumption that 'personalised' approaches are necessarily superior for prevention and screening.